A retrospective view of software maintenance and reengineering research – a selection of papers from European Conference on Software Maintenance and Reengineering 2010. Issue 6 (5th July 2011) - Capilla, Rafael; Dueñas, Juan C.; Ferenc, Rudolf; Capilla, Rafael; Dueñas, Juan C.; Ferenc, Rudolf
SUMMARY As a summary of past, current, and future trends in software maintenance and reengineering research, we give in this editorial a retrospective look from the past 14 years to now. We provide insight on how software maintenance has evolved and on the most important research topics presented in the series of the European Conference on Software Maintenance and Reengineering. Copyright © 2011 John Wiley & Sons, Ltd.